(untitled) (Research, Society and Development, 2022)
This study was intended to analyze the perception of School Physical Education teachers about training and pedagogical practice for the application of the theme of Fights. The methodological path was characterized by an exploratory investigation, whose approach is quanti-qualitative. The participants were six (06) Physical Education teachers from the municipal network of Fortaleza-Ceará. Data were collected by means of an online questionnaire, through the Google Forms Platform and analyzed using Bardin’s content analysis (2011). In the results, it was found that, despite the changes proposed in recent decades with regard to the understanding of fights at school, there is still limited approximation of the participants about the thematic unit of fights in initial training, due to its absence in the curriculum matrices or its insufficient approach. These data contribute to new reflections on the importance of Physical Education in the training and development of a critical, autonomous and protagonist citizen, through planned, inclusive, democratic and integral work, expanding training possibilities, guaranteeing the right of students to experience, discuss and take ownership of the most diverse bodily practices. Therefore, it is proposed that teachers who teach in primary education seek to carry out readings and studies that involve the insertion of fights in School Physical Education classes, with a view to assigning a greater meaning to this cultural manifestation produced and transformed with the development of mankind.